2020
DOI: 10.4103/jehp.jehp_401_20
|View full text |Cite
|
Sign up to set email alerts
|

Communication apprehension and level of anxiety in the medical students of Rafsanjan University of Medical Sciences

Abstract: BACKGROUND: Communication apprehension (CA) is the fear or anxiety about communicating. This study was designed to investigate the CA and its related factors in the medical students at Rafsanjan University of Medical Sciences (RUMS). MATERIALS AND METHODS: In this cross-sectional study, personal report of CA (PRCA-24) was administered to 340 medical and paramedical students to measure anxiety in four domains of large groups, small groups, public speaking, and dyadic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Furthermore, the existence of a correlation between exam stress and being supervised by mentors as the most significant subscale among all the motivational beliefs subscales demonstrates that the students with more exam anxiety may seek mentors more than those with less exam anxiety as one of the central roles of mentors is helping mentees to cope with stress. [ 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the existence of a correlation between exam stress and being supervised by mentors as the most significant subscale among all the motivational beliefs subscales demonstrates that the students with more exam anxiety may seek mentors more than those with less exam anxiety as one of the central roles of mentors is helping mentees to cope with stress. [ 27 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to identify if there is any particularity in young people who apply for healthcare profession programmes that may increase anxiety in social contexts. Earlier contributions from cross-sectional studies also found moderate scores in communication apprehension in health students attending nursing [68,69], radiology [69], and pharmacy [68] programmes.…”
Section: Discussionmentioning
confidence: 81%
“…Individual factors : Gender was found to be positively associated with CA in 6 out of 9 studies that analyzed gender and CA, with female students reporting higher CA than male students in several studies (Anacleto de Araújo et al, 2022; A. M. Kerr & Thompson, 2022; Lang et al, 1998; McCroskey et al, 1983;O'Donnell, 1998; Pierce, 2016). Three out of 9 studies found no significant differences in CA based on gender (Hashemi et al, 2020; LaRochelle & Karpinski, 2016; Rogers & King, 2012). Age was found to be associated with CA in some studies, with younger students reporting higher levels of CA in two studies (O'Donnell, 1998; Pierce, 2016), but no significant association was found in another study (LaRochelle & Karpinski, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies reported age demographics. Two studies found a negative association between lower socioeconomic status and CA, with students from lower socioeconomic backgrounds reporting lower CA than their peers from higher socioeconomic backgrounds (Hashemi et al, 2020; Lang et al, 1998). In terms of race/ethnicity, Asian pharmacy students were found to have higher levels of CA than their Caucasian and black/African American peers (LaRochelle & Karpinski, 2016; McCroskey et al, 1983), while no significant association was found between races in nursing students (Pierce, 2016).…”
Section: Resultsmentioning
confidence: 99%